Metric Survey Specifications for Cultural Heritage. - Bryan, Paul (English Heritage Publishing, 2013)
A revised and updated second edition of Metric Survey Specifications for English Heritage? the standard specification that English Heritage has successfully used to procure metric survey for the last 9 years.